APPLICATION OF BIOPRODUCTS AND COMPLEX FERTILIZERS IN THE TECHNOLOGY OF GROWING AGRICULTURAL CROPS - Олепір, Роман; Ласло, Оксана; Воропін, Петро (SWorldJournal, 2025)
To achieve high yields, it is important to search for and implement modern effective technologies for growing crops. Increasing productivity is possible due to a set of conditions, which include the use of macro- and microfertilizers, biological products.